Guidelines for endoscopic diagnosis of early gastric cancer. Issue 5 (9th July 2020) - Yao, Kenshi; Uedo, Noriya; Kamada, Tomoari; Hirasawa, Toshiaki; Nagahama, Takashi; Yoshinaga, Shigetaka; Oka, Masashi; Inoue, Kazuhiko; Mabe, Katsuhiro; Yao, Takashi; Yoshida, Masahiro; Miyashiro, Isao; et al.
Abstract : The Japan Gastroenterological Endoscopy Society developed the Guideline for Endoscopic Diagnosis of Early Gastric Cancer based on scientific methods. Endoscopy for the diagnosis of early gastric cancer has been acknowledged as a useful and highly precise examination, and its use has become increasingly more common in recent years. However, the level of evidence in this field is low, and it is often necessary to determine recommendations based on expert consensus only. This clinical practice guideline consists of the following sections to provide the current guideline: [I] Risk stratification of gastric cancer before endoscopic examination, [II] Detection of early gastric cancer, [III] Qualitative diagnosis of early gastric cancer, [IV] Diagnosis to choose the therapeutic strategy for gastric cancer, [V] Risk stratification after endoscopic examination, and [VI] Surveillance of early gastric cancer.